Penciptaan Manusia dan Awal Mula Jatuhnya Manusia kedalam Dosa - Jesica Carolina; Jhon Rafael; Martesa Martesa; Sarmauli Sarmauli (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The Biblical concept of sin comes from a review of the term sin used in the Old and New Testaments. Sin is an act of principle, error and pollution. The purpose of this research is to understand how the Bible tells about the condition of humans after they fell into sin, humans began to know the name of suffering, humans began to try with their own strength and humans had to work. This research method uses a qualitative method using the literature study method.